1998
DOI: 10.1111/j.1574-6968.1998.tb13151.x
|View full text |Cite
|
Sign up to set email alerts
|

A second European collaborative study on polymerase chain reaction forToxoplasma gondii, involving 15 teams

Abstract: In order to investigate the accuracy and practicability of the polymerase chain reaction (PCR) in the antenatal diagnosis of congenital toxoplasmosis, a collaborative study involving 15 European laboratories was performed under the auspices of the Biomed 2 Programme of the European Community. Each team received 12 aliquots (four negative, eight positive) of 'artificial samples' made of amniotic fluid spiked with tachyzoites of the RH strain of Toxoplasma gondii. Each team performed its own PCR protocol (all we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In this study, T. gondii DNA was detected only in 2/5 IgM positive women who have had spontaneous abortions and 3/11 women showed no evidence of infection by PCR, though IgG antibodies were detected. This can be attributed to the presence of a long standing immunity to toxoplasmosis or cross-reactive antibodies [ 58 , 59 ] and confirm the sensitivity and specificity of PCR analysis for detecting recent infection in early pregnancy [ 60 ]. This is in agreement with previous reports that PCR is recommended over serologic techniques for diagnosis of toxoplasmosis [ 61 63 ].…”
Section: Discussionmentioning
confidence: 68%
“…In this study, T. gondii DNA was detected only in 2/5 IgM positive women who have had spontaneous abortions and 3/11 women showed no evidence of infection by PCR, though IgG antibodies were detected. This can be attributed to the presence of a long standing immunity to toxoplasmosis or cross-reactive antibodies [ 58 , 59 ] and confirm the sensitivity and specificity of PCR analysis for detecting recent infection in early pregnancy [ 60 ]. This is in agreement with previous reports that PCR is recommended over serologic techniques for diagnosis of toxoplasmosis [ 61 63 ].…”
Section: Discussionmentioning
confidence: 68%
“…It is strongly suggested that individual laboratories should carry out their own characterization if these parameters are modified, and even if no parameter is modified at all. To this aim, a series of “reference samples” should be maintained and provided by a “reference laboratory” to any laboratory intending to establish and maintain an accurate diagnostic test 41 . The organization of training sessions by these reference laboratories would also help to share experience and knowledge about the use of a given protocol, and would harmonize the practices and decision rules.…”
Section: Discussionmentioning
confidence: 99%
“…The development of quantitative real-time PCR (qrt-PCR) has therefore brought to this diagnosis not only robustness but also the possibility of quantifying parasitic loads (4), with the aim of establishing a correlation with the severity of the disease (5,6). Yet the molecular diagnosis of toxoplasmosis essentially relies upon laboratory-developed methods and still suffers from lack of standardization (7,8). This in turn leads to variations in the performances (essentially in sensitivity) of the PCR assays (9,10) and hence in the quality of patient management.…”
mentioning
confidence: 99%